Advances in Network-Based Information Systems The 27th International Conference on Network-Based Information Systems (NBiS-2024) - Barolli, Leonard (Lecture Notes on Data Engineering and Communications Technologies, 2024)
XXVII, 546 p. 335 illus., 250 illus. in color.